MURŪNAH IJTIHĀD JAM‘IYYAH NAHḌAH AL-‘ULAMA: Min Fiqh al-Ḥaḍārah ilā Dīn al-‘Ishrīn (State Islamic University (UIN) of Sunan Ampel Surabaya, 2023)
This Research aims at reviewing the formation of Ijtihad of Nahdlatul Ulama in the various movements and activities for welcoming the centenary of its establishment. Nahdlatul Ulama is the biggest Muslim Organization in Indonesia that has strategic role in assisting the Muslim society. It can be seen in many confusion and dynamic of contemporary lives. Nahdlatul Ulama plays an important role in exposing people on humanism and civilization. The strategic issues concerning interreligious violence, social inequality, economic disfranchise and various other issues regarding human problems faced by people that become special concern of Nahdlatul Ulama. With the eve its centenary, Nahdlatul Ulama applies plans and strategy by arranging forums of fiqh peradaban (civilization-based Islamic jurisprudence) and Religion of Twenty in the effort of constructing responsive and progressive ijtihad in providing the solution of human problems. Through the library research, it is discovered that the construction of Islamic jurisprudence in fiqh peradaban forum and Religion of Twenty is conducted through maqasid al-shari’ah.